Wireless Communications Systems and Networks - Guizani, Mohsen. (Information Technology: Transmission, Processing and Storage, 2004)
Since the early 1990s, the wireless communications field has witnessed explosive growth. The wide range of applications and existing new technologies nowadays stimulated this enormous growth and encouraged wireless applications. The new wireless networks will support heterogeneous traffic, consisting of voice, video, and data (multimedia). This necessitated looking at new wireless generation technologies and enhance its capabilities. This includes new standards, new levels of Quality of Service (QoS), new sets of protocols and architectures, noise reduction, power control, performance enhancement, link and mobility management, nomadic and wireless networks security, and ad-hoc architectures. Many of these topics are covered in this textbook. The aim of this book is research and development in the area of broadband wireless communications and sensor networks. It is intended for researchers that need to learn more and do research on these topics. But, it is assumed that the reader has some background about wireless communications and networking. In addition to background in each of the chapters, an in-depth analysis is presented to help our readers gain more R&D insights in any of these areas. The book is comprised of 22 chapters, written by a group of well-known experts in their respective fields. Many of them have great industrial experience mixed with proper academic background.